The Effect of Material Variations on Discbrakes to Reduce the Heat that Occurs When Braking Using Transient Thermal Simulation - Rifki Maulana; Deri Teguh Santoso Boni (CV. Rayyan Dwi Bharata, 2024)
Indonesia is one of the countries with the most accident statistics in Southeast Asia, where Indonesia is in fifth position. Where the number of traffic accidents in Indonesia, one of which is caused by brake failure, reaches 31%. Therefore, a reliable and good braking system is very necessary to maintain the safety of drivers of both two-wheeled and four-wheeled traffic vehicles. One of the components that plays a very important role in the braking system is the disc brake, and in this case the greater the heat produced, the smaller the braking effectiveness. So this research aims to find out with the existing variations, which one is better able to reduce the heat that occurs when braking takes place. The method used in this research is transient thermal simulation in Solidworks 2022 software, the disc brake diameter used is 180mm and the material variations used are AISI 304, AISI 1020, and Alloy 1060. The conductivity of each material is AISI 304 16W respectively. /m.K, AISI 1020 47W/m.K, and Alloy 1060 200W/m.K. The results obtained from simulations with AISI 304 material, minimum temperature of 1.995ºC, maximum temperature of 2.172ºC, AISI 1020 material, minimum temperature of.996ºC, maximum temperature of 2.185ºC, and for Alloy 1060 material, minimum temperature of 1.996ºC, maximum temperature of 2.224ºC. The conclusion obtained from this research is that materials that have high thermal conductivity values tend to be able to withstand temperatures better during braking